Stress, Depressive Symptoms, and Maternal Self-Efficacy in First-Time Mothers: Modelling and Predicting Change across the First Six Months of Motherhood - Law, K.; Dimmock, J.; Guelfi, K.; Nguyen, T.; Gucciardi, Daniel; Jackson, B. (Wiley-Blackwell Publishing, 2018)
Background: First-time mothers commonly experience stress and depressive symptoms in the postpartum period. Maternal self-efficacy has been shown to be an important protective factor against these experiences; however, research on the dynamic nature of stress, depressive symptoms, and maternal self-efficacy is limited. The aim of this study was to document changes in these psychological factors among first-time mothers, and determine how early maternal self-efficacy perceptions may predict change in stress and depressive symptoms over the first 6 months postpartum. Methods: Sixty first-time Australian mothers were recruited during their third trimester of pregnancy. Participants completed a baseline survey during the third trimester of pregnancy (M = 32.87 weeks, SD = 2.62 weeks), and subsequently reported stress, depressive symptoms, and maternal self-efficacy every 3 weeks postpartum for 6 months. Latent growth curve modelling was used to estimate participants’ change over time for stress and depressive symptoms. Results: First-time mothers’ stress and depressive symptoms peaked, and maternal self-efficacy was weakest, at 3 weeks postpartum. Maternal self-efficacy at 3 weeks postpartum was a significant (negative) predictor of 3-week levels of, and also (positively) predicted later reductions in, stress. Conclusion: Future interventions aimed at bolstering early maternal self-efficacy may protect against postpartum stress for first-time mothers.